Effect of two dose level ~f FSH on superovulatory response, total and viable embryo recovery in Holstein Friesian x Sahiwal crossbred cows with repeated flushing - PATEL, D V; SINGH, S P; NIKHATE, R V; PANCHAL, A G; KASIRAJ, R (The Indian Journal of Animal Reproduction, 2007)
The Holstein Friesian x Sahiwal (HF x S) donor cows were selected randomly and distributedin to two groups (A&B). A total of 32 & 42 embryo flushings in group A & B respectively wereperformed superovulation was achieved by treatment with 200 mg FSH in group A and 400 mg FSH,in group B. the schedule comprised of 8 equal doses between day 9 and 11 post estrus ( day O is dayof standing estrus). Estrus was induced by injecting single dose of Prostaglandin F2a 48 hr. from firstFSH injection. Artificial insemination (AI) was carried out with frozen semen on day 7 post estrous.Donors were flushed non surgically and revealed no embryo recovery in 5 animals (15 .63%) of groupA and 7 animals (16.67%) of group B. The analysis was done-with respect to dose regimen (50% Vs 100%) and repeated flushings (1'1, 2nd and 3rd flush) within the group and between the groups. Themean of ovulation, anovulatory follicles, and viable embryo recovery (VE) with respect to the twoFSH regimen revealed no significant difference (P
Keywords: FSH; Superovulation; Embryo recovery; Flushing; Cow